Experimental Poetry and the Aesthetics of Resistance in Agitated Times - Pérez Villalón, Fernando (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2021)
This article proposes an overview of practices in recent Chilean experimental poetry that explore the diverse dimensions and limits of language as a medium, thus bringing into question what Ulm and Martoni have called our “rituals of perception.” These works by Martín Gubbins, Felipe Cussen, and Pía Sommer not only explore the acoustic, visual, performative, material, and intermedial potentialities of language and literature, they also bring them to the point of a crisis—for instance, in producing works that give up verbal language altogether or works that stubbornly resist the transmission of meaning as the main function of verbal language. The article describes some of these practices and proposes an aesthetic and political interpretation of them along the lines advanced by theoreticians such as Hans Ulrich Gumbrecht (production of presence), Jacques Rancière (the distribution of the sensible), Marjorie Perloff (un-creative writing), Maurizio Lazzarato (a-signifying semiotics).